Body dissatisfaction in Brazilian schoolchildren: prevalence and associated factors - Pinheiro,Andréa Poyastro (2006)
OBJECTIVE: To examine the prevalence of body dissatisfaction and associated factors in 8- to 11-year-old schoolchildren. METHODS: A cross-sectional study including children aged 8- to 11-years enrolled in public and private schools in Porto Alegre, Southern Brazil, was carried out from August to December, 2001. A total of 901 subjects were selected through cluster sampling. Participants answered a questionnaire aimed at measuring body dissatisfaction and self-esteem and questions about family and social pressures on weight change. Height and weight were measured. The relationship between body dissatisfaction and the variables studied was measured by logistic regression. RESULTS: The prevalence of body dissatisfaction was 82%. Fifty-five percent of the girls wanted a thinner body size, and 28% desired a larger one; the estimates for the boys were 43% and 38%, respectively. Children with the lowest self-esteem (OR=1.80; 95% CI: 1.13-2.89) and who thought their parents (OR=6.10; 95% CI: 2.95-12.60) and friends (OR=1.81; 95% CI: 1.02-3.20) expected them to be thinner showed a higher chance of presenting body dissatisfaction. CONCLUSIONS: Body dissatisfaction was highly prevalent among the evaluated schoolchildren, especially in those with lower self-esteem and who thought their parents and friends expected them to be thinner.